Government Bonds - Coyle, Brian (Canterbury, United Kingdom Financial World Publishing, 2002)
This book is a practical guide to international government bonds, explaining their characteristics and then examining in turn the bond markets of the UK, US, Germany and Japan. It describes the instruments for borrowing, the markets for long-term borrowing and liquidity.
Includes index
On the cover "Debt & Equity Markets"
gau 04/08/16
Loan
Keywords: Government securities; Government bond